Purification, crystallization and preliminary X-ray analysis of haemoglobin I from the armoured catfish Liposarcus anisitsi - Smarra, ALS; de Azevedo, W. F.; Fadel, V; Delatorre, P.; Dellamano, M.; Colombo, M. F.; Bonilla-Rodriguez, G. O. (Munksgaard Int Publ Ltd, 2000)
Liposarcus anisitsi is an armoured catfish that presents accessorial air oxygenation through a modified stomach, which allows this species to survive in waters with very low oxygen content. Analysis of its haemolysate has shown the presence of four haemoglobins; this work focuses on the main component, haemoglobin I. It has been crystallized in two different forms and X-ray diffraction data have been collected to 2.77 and 2.86 Angstrom resolution using synchrotron radiation. Crystals were determined to belong to the space groups C2 and P2(1) and preliminary structural analysis revealed the presence of one tetramer in the asymmetric unit in both crystal forms. The structure was determined using a standard molecular-replacement technique.